Biosurfactant as a promoter of methane hydrate formation: thermodynamic and kinetic studies - Arora, Amit; Cameotra, Swaranjit Singh; Kumar, Rajnish; Balomajumder, Chandrajit; Singh, Anil Kumar; Santhakumari, B.; Kumar, Pushpendra; Laik, Sukumar (Scientific Reports, 2016)
Natural gas hydrates (NGHs) are solid non-stoichiometric compounds often regarded as a next generation energy source. Successful commercialization of NGH is curtailed by lack of efficient and safe technology for generation, dissociation, storage and transportation. The present work studied the influence of environment compatible biosurfactant on gas hydrate formation. Biosurfactant was produced by Pseudomonas aeruginosa strain A11 and was characterized as rhamnolipids. Purified rhamnolipids reduced the surface tension of water from 72 mN/m to 36 mN/m with Critical Micelle Concentration (CMC) of 70 mg/l. Use of 1000 ppm rhamnolipids solution in C type silica gel bed system increased methane hydrate formation rate by 42.97% and reduced the induction time of hydrate formation by 22.63% as compared to water saturated C type silica gel. Presence of rhamnolipids also shifted methane hydrate formation temperature to higher values relative to the system without biosurfactant. Results from thermodynamic and kinetic studies suggest that rhamnolipids can be applied as environment friendly methane hydrate promoter.

Effect of different fixed bed media on the performance of sodium dodecyl sulfate for hydrate based CO2 capture - Arora, Amit; Kumar, Asheesh; Bhattacharjee, Gaurav; Kumar, Pushpendra; Balomajumder, Chandrajit (Materials & Design, 2016)
Sodium Dodecyl Sulfate (SDS) is used as a kinetic promoter in gas hydrate formation. In this work, the performance of SDS for carbon dioxide gas hydrate formation in two different fixed bed media: silica sand and zeolite (5A and 13X) has been evaluated. The concentration of SDS was fixed at 0.5 wt%. The experiments were carried out in batch mode with the initial pressure fixed at 3.0 MPa, and the temperature kept constant at 274.65 K. The results showed that hydrate of carbon dioxide with fixed bed of silica sand was significantly promoted by the addition of SDS as compared to the other fixed bed medium used in this study: zeolite 13X. (c) 2015 Elsevier Ltd. All rights reserved.
Keywords: Carbon dioxide; Fixed bed media; Hydrate formation; Kinetic promoter; Silica sand; Zeolite 5A and 13X

Role of Rhamnolipid: A biosurfactant in methane gas hydrate formation kinetics - Arora, Amit; Cameotra, Swaranjit Singh; Kumar, Rajnish; Singh, Anil Kumar; Kumar, Pushpendra; Balomajumder, Chandrajit; Laik, Sukumar (Proceedings of The First International Conference on Recent Advances in Bioenergy Research, 2016)
Naturally occurring methane gas hydrate is a vast source of methane gas which is trapped in crystalline ice-like structure present in permafrost regions and under the sea in outer continental margins. It is purposed that total amount of carbon in the form of methane hydrates is almost twice the carbon content in all the fossil fuel reserves put together, and hence these are supposed to be the future potential energy resource. This paper investigates the laboratory investigations on effect of a biosurfactant rhamnolipid on methane hydrate formation kinetics. Rhamnolipid was produced by Pseudomonas aeruginosa strain A11. The presence of P. aeruginosa has been reported in Gulf of Mexico gas hydrate samples. Biosurfactant reduced the surface tension of water from 72 to 36 mN/m with CMC of 70 mg/L. The biosurfactant dose is studied at two different concentrations in the solution at 100 and 1000 ppm. Kinetic of hydrate formation and growth is compared at 0, 100, and 1000 ppm of rhamnolipid showing that rhamnolipid acts as a hydrate promoter at these concentrations. Thus, small dosages of rhamnolipids produced by P. aeruginosa strain A11 must clearly affect the gas hydrate formation kinetics in natural sites (as in Gulf of Mexico).
Keywords: Induction time; methane hydrate; Potential energy resource; Pseudomonas aeruginosa; Rhamnolipid

Co9Se8 nanoparticles as high capacity anode material for lithium-ion batteries - Kumar, Pushpendra; Hu, Lung-Hao (Materials Research Express, 2018)
Present investigation deal with the facile synthesis of Co9Se8 nanoparticles (NPs) and their application as the potential anode for lithium-ion battery (LIB). The primary size of the Co9Se8 NPs can be achieved between 10 similar to 25 nm while the secondary cluster size ranging from 150 similar to 200 nm as observed by transmission electron microscope (TEM). The specific capacity of Co9Se8 NPs LIB anode can reach around similar to 610 mAhg(-1) during charging (lithium ion released from Co9Se8 nanoparticles), and -730 mAhg(-1) during discharging (lithium ion intercalated) at an applied current density of similar to 100 mAg(-1). These values are significantly higher than that of the commercial graphite anode (theoretical capacity similar to 372 mAhg(-1)). The irreversibility of Co9Se8 anode (similar to 15%) is also significantly lower than that of most metal oxides and silicon-based anodes (irreversibility ranging between 30 similar to 50% or higher for Si). The reason for superior specific capacity and low irreversibility compared to metal oxides and silicon-based materials could be owing to the stable nano-cluster size which help to reduce the diffusion path and internal resistance to lithium ion.
Keywords: irreversibility; lithium-ion battery; lithium-ion diffusion; Nanoparticles; specific capacity

Investigations on optical properties of ZnO decorated graphene oxide (ZnO@GO) and reduced graphene oxide (ZnO@r-GO) - Kumar, Pushpendra; Som, Sudipta; Pandey, Mukesh K.; Das, Subrata; Chanda, Anupama; Singh, Jai (Journal of Alloys and Compounds, 2018)
The present investigation is based on the production of reduced graphene oxide (r-GO) from the graphene oxide using Hummer's (GO) and improved Hummer's methods (IGO) at elaborated conditions, named as GO and IGO, respectively hereafter. In contrast to previously known techniques, the presented process does not generate toxic gas. Meanwhile, the reduction temperature can be easily controlled. This approach provides a more significant amount of hydrophilic oxidized graphene as compared to GO and IGO with the use of additional KMnO4. Thus synthesized IGO was used to produce r-GO by thermal treatment. The morphological characteristics show that the obtained samples have a wrinkled paper-like morphology with severely folded lines. However, r-GO has double layers and multilayer at the edges. All the products (GO, IGO, and r-GO) have been decorated with ZnO nanoparticles (NPs). The XRD patterns of ZnO@GO composites have confirmed the characteristic peaks of wurtzite ZnO indicating the formation of ZnO nanoparticles onto the surface of graphene. The microscopic studies confirm the random growth/decoration of ZnO NPs on the surface of GO/IGO/r-GO sheets. However, in IGO and r-GO, loading/growth of ZnO NPs are less as compared to ZnO@GO. Overall structural studies indicate the oxidation of graphite and reduction of graphene oxide into r-GO sheets and ZnO decoration. Upon UV excitations, a bright blue emission has been exhibited by the GO that originates from geminate recombination of localized e-h pairs in sp(2) clusters those primarily act as the luminescent centers. The noteworthy enhancement in the emission intensities after the incorporation of ZnO nanoparticles on the surface of GO is observed. The improved synthesis method and low-temperature reduction technique of GO may be essential for the large-scale production of r-GO as well as the construction of devices composed of ZnO@GO/IGO/r-GO. (C) 2018 Elsevier B.V. All rights reserved.

Controlled synthesis of two-dimensional (2-D) ultra-thin bismuth selenide (Bi2Se3) nanosheets by bottom-up solution-phase chemistry and its electrical transport properties for thermoelectric application - Bin Masood, Khalid; Kumar, Pushpendra; Giri, Rajiv; Singh, Jai (FlatChem, 2020)
Bismuth Selenide and associated compounds inheriting stacked layered structure represent a unique class of materials where bulks are insulating with conducting surfaces, best known as thermoelectric materials. The bottom-up solution-based approach is a convenient alternative producing ultrathin high quality two-dimensional Bi2Se3 nanosheets. The present investigation deals with glycol mediated synthesis of highly crystalline ultrathin Bi2Se3 nanosheets. The as-synthesized Bi2Se3 nanosheets exhibit a rhombohedral crystal structure with a substantial surface-to-volume ratio that can possess several potential applications. Besides, the ultrathin Bi2Se3 nanosheets produced herein, found to be n-type with robust spatial confinement of charge carriers advantageous for thermoelectric applications, delivering a high-power factor of 1.55 mu W/cmK(2) at 150 degrees C. The method demonstrates the generic feature of the solution phase technique for the synthesis of highly crystalline nanosheets allowing mass production of identical ultra-thin nanosheets that can be easily integrated into devices for several promising applications, including spintronics, energy storage, and topological quantum computation.
Keywords: Rhombohedral structure; Sheet-like structure; Thermoelectric nanomaterials; transmission electron microscopy; XPS Spectra

Electrochemical performance of pre-lithiated ZnMoO4 and r-GO@ZnMoO4 composite anode for lithium-ion battery application - Bin Masood, Khalid; Parte, Golu; Jain, Neha; Dwivedi, Pravin K.; Kumar, Pushpendra; Shelke, V, Manjusha; Patel, Rp; Singh, Jai (Journal of the Taiwan Institute of Chemical Engineers, 2020)
Exploring a safer replacement of Li metal anode is crucial for technological, and fundamental importance. Li-metal is a preferred choice as anode material for lithium-ion battery (LIB) applications. However, parasitic dendritic growth on the Li metal surface during cycling causes instability and safety dreads. In the present study, we have investigated that the pre-lithiated ZnMoO4 is superior to its carbon-based counterparts (r-GO@ZnMoO4), moreover safer and sustainable than Li metal anode. The pre-lithiated ZnMoO4 delivers a better reversible capacity (similar to 1000 mAhg(-1) at 0.1 Ag-1), superior rate capability (similar to 400 mAh g(-1) at 2 Ag-1), and excellent cycling stability over 300 cycles at 0.1 Ag-1, as compared to bare ZnMoO4 and r-GO@ZnMoO4 composite. The present investigation is an attempt to provide a substitute for commonly used Li-metal/carbon anodes with better performance. (C) 2020 Taiwan Institute of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Cycling stability; Electrochemistry; Li-ion battery; Nyquist plot; Rate performance; ZnMoO4 nanocomposites

Comprehensive tutorial on the pulsed laser deposition technique and developments in the fabrication of low dimensional systems and nanostructures - Masood, Khalid Bin; Kumar, Pushpendra; Malik, Mushtaq Ahmad; Singh, Jai (Emergent Materials, 2021)
Pulsed laser deposition (PLD) is a simple and extremely versatile technique to grow thin films and nanomaterials of a wide variety of materials. PLD allows the deposition of profoundly different materials, including high-temperature superconductors, oxides, nitrides, carbides, semiconductors, metals, and even polymers or fullerenes with high deposition rates. Growing thin films using PLD is now being used around the world for prototyping thin films of many inorganic materials and even in device fabrication protocols. This article covers the detailed development, versatility, and reliability of the ultraviolet (UV) excimer laser. It is envisioned that this review article is of interest for both the materials and chemical scientists engaged in more fundamental aspects of pulsed laser ablation and deposition. The present article highlights the historical developments of PLD technique, complete mechanism of thin film fabrication, optimization of the quality of thin films and the fabrication of thin films of the materials like ZnO, Graphene, MoS2, and WS2 which are being explored for various potential applications.

Hydrate-based carbon capture process: assessment of various packed bed systems for boosted kinetics of hydrate formation - Arora, Amit; Kumar, Asheesh; Bhattacharjee, Gaurav; Balomajumder, Chandrajit; Kumar, Pushpendra (Journal of Energy Resources Technology-Transactions of the ASME, 2021)
The case for developing novel technologies for carbon dioxide (CO2) capture is fast gaining traction owing to increasing levels of anthropogenic CO2 being emitted into the atmosphere. Here, we have studied the hydrate-based carbon dioxide capture and separation process from a fundamental viewpoint by exploring the use of various packed bed media to enhance the kinetics of hydrate formation using pure CO2 as the hydrate former. We established the fixed bed reactor (FBR) configuration as a superior option over the commonly used stirred tank reactor (STR) setups typically used for hydrate formation studies by showing enhanced hydrate formation kinetics using the former. For the various packing material studied, we have observed silica gel with 100 nm pore size to return the best kinetic performance, corresponding to a water to hydrate conversion of 28 mol% for 3 h of hydrate growth. The fundamental results obtained in the present study set up a solid foundation for follow-up works with a more applied perspective and should be of interest to researchers working in the carbon dioxide capture and storage and gas hydrate fields alike.
Keywords: air emissions from fossil fuel combustion; Carbon dioxide capture; combustion of waste; Fixed bed reactor; fuel combustion; Gas hydrate; hydrates; kinetics; Silica gel

MoSx surface-modified, hybrid core-shell structured LiFePO4 cathode for superior Li-ion battery applications - Hu, Lung-Hao; Kumar, Pushpendra (Journal of Alloys and Compounds, 2021)
A hybrid core-shell cathode, composed of MoSx shell and carbon-coated lithium iron phosphate core (MoSx@cLiFePO(4) or MoSx@c-LFP) is obtained by the post-annealing of a thermally decomposable ammonium thiomolybdate and commercial carbon-coated LiFePO4 (c-LFP) powder. The specific capacity of the commercially available amorphous carbon-coated LFP (c-LFP) is typically around 120-160 mAhg(-1), which is usually lower than the theoretical values similar to 170 mAhg(-1) due to the limited Li+ phase-boundary diffusion and low electrical conductivity. In the present investigation, we report that the specific capacity of surfacemodified (similar to 1.2 wt% of layered MoSx) c-LFP (MoSx@c-LFP) material can reach as high as similar to 228 mAhg(-1) delivering high gravimetric energy density similar to 750-770 Whkg(-1). The excess capacity can be attributed to the partial Li-ions intercalated/de-intercalated through the MoSx layers within a specific potential range (2.0-3.8 V). MoSx coating helps increase the c-LFP surface's stability by forming strong covalent bonding and is believed to enhance the electronic conduction by reducing the interparticle contact. During charge and discharge the hysteresis is substantially reduced by MoSx coating. The approach may open up a universal route to increase the cathode capacity, potentially attractive for further Li-ion battery research and industrial applications. (C) 2021 Elsevier B.V. All rights reserved.
Keywords: Ammonium thiomolybdate; Coulombic efficiency; Hybrid core-shell cathode; hysteresis; MoSx

Rhamonolipids produced by Pseudomonas aeruginosa promotes methane hydrates formation in fixed bed silica gel medium - Arora, Amit; Cameotra, Swaranjit Singh; Balomajumder, Chandrajit; Kumar, Rajnish; Singh, Anil Kumar; Santhakumari, B.; Kumar, Pushpendra; Laik, Sukumar (Marine Geophysical Research, 2021)
Natural gas hydrates are seen as an alternative future energy source. They have also been valued for their carbon dioxide capturing capability, gas separation, desalination, natural gas storage and transportation. Developing economical and viable gas hydrate based technology is one of the most promising research areas of present decade. Successful commercialization of gas hydrate based technology is often curtailed due to slow formation rate. The present study evaluates biosurfactant as a kinetic promoter of methane hydrates formation in a fixed bed C type silica gel medium. Biosurfactant was produced by growing Pseudomonas aeruginosa strain A11 in glycerol supplemented mineral salt medium. Biosurfactant characterization with FTIR, NMR and MALDI-TOF spectroscopy reveled it to be a glycolipids type biosurfactant namely rhamnolipids. Saturating C type silica gel with of 100 ppm rhamnolipids solution enhanced the rate of methane hydrates formation by reducing the induction time. Mole of methane consumed and percentage of water to hydrate conversion was observed to be more in 1000 ppm rhamnolipids saturated C type silica gel as compared to quiescent water system and water saturated silica gel system. Overall results suggest that rhamonolipids produced by strain A11 in combination with silica gel can be utilized as environmentally safe kinetic promoter for methane hydrate formation.
Keywords: Biosurfactant; Energy; Glycolipids; Induction time; Kinetic promoter